A Development of English Listening and Speaking Skills Through Natural Approach for Grade 9 Students at Watsidok School, Phrae - Kaewthammanukul, Pornsawan; Anchunda, Henry Yuh (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to compare the English listening and speaking skills of grade 9 students after using Natural Approach with the A2 level of the CEFR. 2) to study the satisfaction of grade 9 students on using the Natural Approach. This research was an experimental research with the one-shot case study design. The samples were purposively selected class of 13 ninth grade students at Watsidok School, Phare Province during the second semester of the academic year 2022. The research instruments were: 1) 6 lesson plans using the Natural Approach. 2) 4 sections of the English listening and speaking assessment test and 3) the students' satisfaction questionnaire on the Natural Approach. The data were analyzed using descriptive statistics, including mean, standard deviation, and percentage. The research results showed that 1) students' English listening and speaking skills after using the Natural Approach are at the A2 level (39.48%) of the CEFR. 2) the satisfaction of grade 9 students on the Natural Approach was at the highest level ( = 4.51, S.D.= 0.63).